Effect of Chromium Metal Accumulation on the Magnesium Absorption and Chlorophyll Content in Vegetables - Sulistiani, Widya Sartika; Widowati, Hening; Sari, Kartika; Sutanto, Agus (UI Scholars Hub, 2021)
This study analyzed the effect of chromium metal accumulation on magnesium absorption and chlorophyll content in vegetables. The effect of accumulation was determined by performing controlled experimental methods on planting media supplemented with chromium and by directly observing vegetables grown in chromium-polluted areas, such as mountain, rice field, street, and industrial areas. The controlled experiments were carried out by varying the chromium contamination (1 and 3 ppm) and magnesium nutrition (0.4, 0.6, and 0.8 g/L) in planting media. The controlled experiment was compared with the results of field observation in several chromium-polluted areas. The effect of the treatment was analyzed based on the chlorophyll and magnesium levels in the leaves in comparison with the chromium levels in the planting medium. The results of observation and controlled experiments showed that the accumulation of chromium in plants affected the absorption of magnesium, which also affected chlorophyll formation and thus disrupted plant growth. The high chromium level (3 ppm) and magnesium level in planting media can reduce the accumulation of chromium in kale stems and leaves by 19% and 33%, respectively, increase magnesium absorption on kale stems and leaves by 7% and 5%, respectively, and increase chlorophyll formation on kale stems and leaves by 12% and 11%, respectively. Field observation in several chromium-polluted areas showed that spinach has a better chromium accumulation tolerance than kale in terms of magnesium absorption. The type of planting media, plant species, and the presence of other metal contaminants also affect chromium accumulation, magnesium absorption, and chlorophyll level.